Method for producing QT1050-5 crankshaft by adopting full waste steel

Through the smelting of all scrap steel and fine chemical treatment, the problem of difficulty in producing high-strength crankshafts in the existing technology is solved, and the production of QT1050-5 crankshafts with low cost and low energy consumption is achieved.

CN119747598APending Publication Date: 2025-04-04YUNNAN YUNNEI POWER MASCH MFR CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411967639.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to produce high-strength crankshafts that meet high precision requirements, and the traditional process costs and energy consumption are high.

Method used

By using all scrap steel for smelting, controlling the chemical composition of molten iron and spheroidization, combining primary, secondary incubation and heat treatment, the QT1050-5 crankshaft was prepared.

Benefits of technology

It is realized that crankshafts with tensile strength of 1050MPa and above without isothermal quenching heat treatment, reducing process costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of metallurgical industry, and particularly relates to a method for producing a QT1050-5 crankshaft by adopting full scrap steel, which comprises the steps of smelting, spheroidizing, primary inoculation, compound strengthening, secondary inoculation, final molten iron chemical component and quality control, iron mold sand-lined molding, pouring, box opening, heat treatment and the like. According to the crankshaft casting obtained through the method, the spheroidization grade is 1-2 grade, the graphite size is 6-8 grade, the pearlite content is 80-95%, the lamellar spacing is 150-300 nm, the tensile strength Rm is larger than or equal to 1050 mpa, the ductility is 5.5%-9%, the hardness is 270-320 HB, and the requirement of the brand QT1050-5 is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgical industry, and specifically relates to a method for producing a QT1050-5 crankshaft by using all scrap steel. Background Art

[0002] The crankshaft is an important component in the engine. Its function is to convert the reciprocating motion of the piston into rotational motion, thereby driving the other parts of the engine. The rotation angle of the crankshaft (crankshaft angle) is measured in degrees, and each change in angle is related to fuel injection, spark plug sparking, and precise mechanical cooperation. The material of the crankshaft is usually ductile iron, and common grades are QT600-3, QT700-2, QT800-2, QT900-2, QT900-5, etc. The current ultimate strength of general ductile iron is 1000MPa. Higher performance ductile iron crankshafts must be achieved by adding a large amount of alloying elements combined with isothermal quenching heat treatment, but this process is costly and energy-intensive.

[0003] On January 4, 2019, the applicant applied for an invention patent named "A method for producing cast QT950-4 crankshafts using all scrap steel" and the application number "CN201910006171.8". The application disclosed how to use scrap steel to produce cast crankshafts with the grade QT950-4. However, with the continuous progress of the automotive industry, the QT950-4 grade can no longer meet the high-precision requirements. Therefore, how to break through the technical barriers and produce higher-strength crankshafts is a major problem facing the crankshaft production industry. Summary of the invention

[0004] The purpose of the present invention is to solve the deficiencies of the prior art and provide a method for producing a QT1050-5 crankshaft using all scrap steel.

[0005] The present invention is achieved through the following technical solutions: S1, smelting, adding raw materials into a medium frequency electric furnace to heat up and smelt molten iron, wherein the raw materials are scrap steel and recycled materials; During the heating process, 3.5-4.0% of the total weight of the scrap steel is added as a low-sulfur recarburizer and 0.8-1.5% of the total weight of the scrap steel is added; after the molten iron is melted to 1500°C, a direct reading spectrometer is used to analyze the chemical composition of the molten iron; According to the analysis results of the direct reading spectrometer, by adding carburizer, ferrosilicon alloy and ferromanganese alloy, the chemical composition of molten iron is controlled to be 3.65-3.75% C; 1.2-1.3% Si; 0.5-0.65% Mn; ≤0.020% S; ≤0.025% P; 0.1-0.15% Cr; 0.2-0.3% Cu; 0.015-0.02% Ni; The time of the whole smelting process is controlled to be ≤50min; after melting, the temperature of the molten iron rises to 1550℃; after the molten iron in the furnace is left to stand for 3-5 minutes, the temperature of the molten iron is adjusted to the outlet temperature of 1510±10℃ before the water is discharged; during the water discharge process, a hanging scale is used to control the amount of molten iron discharged each time; S2, spheroidizing treatment, primary inoculation and composite strengthening, spheroidizing treatment is carried out by flushing method, spheroidizing agent is added to the spheroidizing bag on the side of the furnace body, the Mg content of the spheroidizing agent is 5-6%, the RE content is 1-2%, the particle size of the spheroidizing agent is 15-25 mm, and the amount of the spheroidizing agent added is 0.95% of the weight of the molten iron; After tamping, a primary inoculant is added for primary inoculation, wherein the primary inoculant is a silicon-barium alloy with a particle size of 3-8 mm, and the amount of the primary inoculant added is 0.4% of the weight of the molten iron; While adding the primary inoculant, the spheroidizing bag is compositely strengthened with Sb, Sn and Cu alloys, and Sb, Sn and Cu are added to the side of the spheroidizing bag where the spheroidizing agent is not added; wherein, the amount of Sb added is 0.005-0.015% of the weight of the molten iron; the amount of Sn added is 0.005-0.015% of the weight of the molten iron; and the amount of Cu added is 0.5-0.65% of the weight of the molten iron; S3, secondary inoculation, after the completion of step S2, the temperature of the molten iron is measured and the water is discharged and the secondary inoculation is carried out with the flow, the secondary inoculant adopts a silicon-barium alloy with a particle size of 3-8mm and a sulfur-oxygen inoculant with a particle size of 2-6mm, the amount of the silicon-barium alloy in the secondary inoculant is 0.3% of the weight of the molten iron, and the amount of the sulfur-oxygen inoculant is 0.15% of the weight of the molten iron; the molten iron obtained after the secondary inoculation is the final molten iron; S4. Chemical composition and quality control of final molten iron. Direct reading spectrometer is used to analyze the chemical composition of the final molten iron. When the C content of the final molten iron is 3.5-3.6%, the Si content is 2.25-2.35%, the Cu content is 0.75-0.85%, the Sn content is 0.008-0.015%, and the Sb content is 0.008-0.015%, the chemical composition is qualified, otherwise the chemical composition is unqualified. At the same time, samples are taken from the final molten iron and poured into thermal analysis. The sample cup is solidified, and the cooling curve of the final molten iron is collected by a thermal analyzer. The cooling curve is analyzed by thermal analysis software. The quality of the final molten iron is controlled according to the analysis results. When the dynamic eutectic index of the final molten iron is 0.7-0.9, the inoculation index is 30-50, the shrinkage index is 0.2-0.45, and the liquidus carbon equivalent is 4.1-4.2, the quality is qualified, otherwise it is unqualified; the final molten iron with unqualified chemical composition and / or quality is returned to step S1 as recycled material; S5, iron mold sand coating molding, control the thickness of the coating sand layer to 5-6mm, iron mold temperature to 100-150℃, after the upper and lower iron molds are combined, glue the pouring cup at the sprue position, and control the pouring cup height to 150-200㎜; S6, pouring, pouring the final molten iron with qualified chemical composition and quality in step S4 from the pouring cup into the iron mold, controlling the pouring temperature to be 1410±10°C, adding a Ce-containing inoculant with a weight of 0.1% of the weight of the final molten iron in the iron mold during the pouring process, wherein the Ce-containing inoculant has a Si content of 68-74% and a Ce content of 1.5%-2.0%; after the final molten iron is poured into the iron mold, the cooling rate of the final molten iron is 0.6-0.65°C / S; From step S2 to step S6, the whole process takes ≤7 minutes; S7, unpacking. After the molten iron is poured, the pouring cup is removed after the molten iron in the pouring cup solidifies. The casting is unpacked and taken out within 20-25 minutes after the pouring is completed. The casting temperature is 600-700℃ when unpacking. After unpacking, the casting is air-cooled to room temperature. S8, heat treatment, heating the casting obtained in step S7 to 880°C-900°C, keeping it at that temperature for 3-4 hours for normalizing treatment; firstly force atomization cooling of the casting after normalizing treatment for 3-4 minutes, then keeping it at that temperature for 4-8 hours at a temperature of 500-550°C for tempering treatment, and then air cooling it to room temperature to obtain QT1050-5 crankshaft casting.

[0006] Preferably, the scrap steel has a C content of 0.2-0.4%, a Si content of 0.25-0.35%, a Mn content of ≤0.8%, a P content of ≤0.03%, and a S content of ≤0.02%. The scrap steel is shot blasted before use to remove rusty impurities on the surface and reduce oxidation of molten iron.

[0007] Preferably, the heating method in step S8 is heating along with the furnace, and the heating rate is 10°C / min.

[0008] The crankshaft casting obtained by the method of the present application has a spheroidization grade of 1-2, a graphite size of 6-8, a pearlite content of 80-95%, a lamellar spacing of 150-300nm, a tensile strength Rm≥1050MPa, an elongation of 5.5%-9%, and a hardness of 270-320HB.

[0009] The forced atomization cooling in step S8 is carried out in a mist cooling device, which is composed of a sealed box, a pipe frame and a fan. The sealed box is a rectangular structure; the pipe frame is arranged in the sealed box, and the fan is arranged on the pipe frame; there are two pipe frames and they are interconnected, the two pipe frames have the same shape and circumference, and the connection between the two pipe frames is in a "cross" shape; a number of oval-shaped mist outlets are evenly opened on the inner side of the pipe frame; the fan covers the mist outlet and is arranged on the pipe frame through a fixing clamp; a connecting pipe is also arranged at the center of the outer side of the two pipe connections, one end of the connecting pipe is connected to the inside of the pipe frame, and the other end passes through the sealed box and is arranged outside the sealed box; a drainage pipe connected to the inside of the sealed box is also arranged at the bottom of the sealed box; a lock for hanging the casting is provided at the center above the pipe frame; one end of the connecting pipe that passes through the sealed box and is arranged outside the sealed box is connected to the mist outlet end of the ultrasonic atomizer, and the drainage pipe is connected to the water inlet end of the ultrasonic atomizer; a surface on the sealed box is movably arranged on the sealed box to form a box door.

[0010] The particle size of the water mist generated by the ultrasonic atomizer is 5 μm; the atomization volume of the mist outlet is 75-90 ml / min, and the wind speed of the fan is 5 m / s-8 m / s.

[0011] Compared with the prior art, the present invention has the following beneficial effects: 1. In the smelting stage, the present application improves the tensile strength, hardness, toughness and impact toughness of the product by precisely controlling the Cr content to 0.1-0.15%, the Cu content to 0.2-0.3% and the Ni content to 0.015-0.02%; 2. The primary and secondary inoculants in the present application use silicon-barium alloy and oxygen-sulfur inoculants. The addition of barium can refine the graphite balls and make the graphite balls more round. The addition of barium inoculation can also prevent the inoculation decay, ensure the inoculation effect, and help improve the strength and toughness of ductile iron; the addition of oxygen-sulfur inoculants can neutralize some harmful trace elements, increase the number of graphite balls, and improve the spheroidization rate, thereby improving the quality and performance of ductile iron, so that the mechanical strength of ductile iron is improved, and the internal defects of castings are reduced; 3. This application also uses Sb, Sn, and Cu alloys to perform composite strengthening on the spheroidizing package after spheroidizing inoculation. The addition of copper can refine the matrix structure, improve the strength and hardness of the ductile iron, and maintain good toughness and corrosion resistance; tin is a strong pearlitizing element, and the addition of tin can promote complete pearlitization of the matrix and compensate for the decrease in pearlite caused by increasing the silicon content; the addition of antimony can improve the roundness of ductile iron graphite and increase the number of graphite balls, thereby improving the strength and hardness of the ductile iron.

[0012] 4. This application controls the chemical composition and quality of the final molten iron to control the C content of 3.5-3.6%, the Si content of 2.25-2.35%, the Cu content of 0.75-0.85%, the Sn content of 0.008-0.015%, and the Sb content of 0.008-0.015%; adopts a low-carbon and high-silicon solution to improve the elongation and toughness of the crankshaft; the dynamic eutectic index is 0.7-0.9, the inoculation index is 30-50, the shrinkage index is 0.2-0.45, and the liquidus carbon equivalent is 4.1-4.2. The contents of C, Si, Cu, Sn, and Sb in the final molten iron entering the casting process are all in the optimal proportion, and the indicators such as the dynamic eutectic index, inoculation index, shrinkage index, and liquidus carbon equivalent are in the optimal range.

[0013] 5. The present application adds a Ce-containing inoculant during the pouring process, wherein the Si content of the Ce-containing inoculant is 68-74% and the Ce content is 1.5%-2.0%. Since a delayed inoculation treatment method is adopted, the decay can be eliminated and the amount of inoculant added can be reduced; the addition of Ce has a stable spheroidizing effect on the molten iron with a hypereutectic composition, and can promote the spheroidization of graphite.

[0014] 6. The time of the entire smelting process in the present application is ≤50min, which avoids oxidation of molten iron caused by long-term smelting; from step S2 to step S6, the entire process takes ≤7min; precise time control can effectively prevent the molten iron in the later stage of pouring from being left for too long, resulting in coarse graphite.

[0015] 7. In this application, the normalizing treatment makes the structure of the ductile iron denser and the strength higher; the tempering treatment improves the toughness and plasticity of the ductile iron, and at the same time, it can eliminate the stress generated by forced atomization cooling and avoid crack defects.

[0016] 8. The forced atomization cooling of the present application is carried out in a special mist cooling device. When the casting is cooled by the mist cooling device, the casting is located in the middle of the pipeline frame, and the mist cooling effect received by each position of the casting is close, thereby achieving three-dimensional uniform spraying, improving the cooling efficiency and ensuring the stability of the casting.

[0017] 9. The crankshaft casting obtained by the method of the present application has a spheroidization grade of 1-2, a graphite size of 6-8, a pearlite content of 80-95%, an interlamellar spacing of 150-300nm, a tensile strength Rm≥1050MPa, an elongation of 5.5%-9%, and a hardness of 270-320HB, meeting the requirements of grade QT1050-5.

[0018] 10. The present application can achieve stable production of crankshaft castings with a grade of QT1050-5 without adopting an isothermal quenching heat treatment process, and the process cost and energy consumption are much lower than those of an isothermal quenching heat treatment process. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic diagram of the pipeline frame structure of the mist cooling device of the present application; Figure 2 A schematic top view of a pipe frame of the mist cooling device of the present application; Figure 3 This is a schematic diagram of the structure of the mist cooling device of the present application; Figure 4 This is a schematic diagram of the fan installation method in the mist cooling device of this application; Figure 5 and Figure 6 The test report of the crankshaft casting for this application; Figure 7 is a microstructure diagram of the crankshaft casting of Example 2; In the figure: 1- pipe frame; 2- mist outlet; 3- fan; 4- fixing clip; 5- lock; 6- casting; 7- sealing box; 8- connecting pipe; 9- drain pipe. DETAILED DESCRIPTION

[0020] The present application is further described below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present application is not limited by the embodiments.

[0021] The forced atomization cooling in all the following embodiments is carried out in a mist cooling device, which is composed of a sealed box 7, a pipe frame 1 and a fan 3. The sealed box is a rectangular parallelepiped structure; the pipe frame is arranged in the sealed box, and the fan is arranged on the pipe frame; the pipe frames are two and interconnected, the shapes and circumferences of the two pipe frames are consistent, and the connection between the two pipe frames is in a "cross" shape; a plurality of oblong mist outlets 2 are evenly opened on the inner side of the pipe frame; the fan covers the mist outlet and is arranged on the pipe frame through a fixing clamp 4; the outer side of the connection between the two pipes is A connecting pipe 8 is also provided in the center, one end of which is connected to the inside of the pipeline frame, and the other end passes through the sealing box and is arranged outside the sealing box; a drainage pipe 9 connected to the inside of the sealing box is also provided at the bottom of the sealing box; a lock buckle 5 for hanging the casting 6 is provided at the center above the pipeline frame; one end of the connecting pipe passes through the sealing box and is arranged outside the sealing box and is connected to the mist outlet end of the ultrasonic atomizer, and the drainage pipe is connected to the water inlet end of the ultrasonic atomizer; a surface on the sealing box is movably arranged on the sealing box to form a box door; the particle size of the water mist generated by the ultrasonic atomizer is 5μm. Example 1

[0022] The raw materials of this embodiment are the plate-shaped steel heads produced by the steel structure factory and the recycled materials produced by the pouring system during the pouring process, wherein the plate-shaped steel heads produced by the steel structure factory are scrap steel, and the materials of the raw materials are Q235 and Q345. The contents of various elements in the scrap steel are shown in Table 1.

[0023] Table 1. Element content in scrap steel of Example 1

[0024] 1700 kg of scrap steel in Table 1 was taken and 300 kg of recycled materials produced by the pouring system during the pouring process were added into the medium frequency electric furnace to heat up and melt the molten iron. The entire smelting process took 48 minutes.

[0025] During the heating process, 65 kg of low-sulfur recarburizer and 17 kg of high-purity silicon carbide were added; after the molten iron was melted to 1500°C, the chemical composition of the molten iron was analyzed by direct reading spectrometer as shown in Table 2.

[0026] Table 2. Chemical composition of molten iron during smelting in Implementation 1

[0027] According to the analysis results of the direct reading spectrometer, the chemical composition of the molten iron is controlled as shown in Table 3 by adding carburizer, ferrosilicon alloy and ferromanganese alloy.

[0028] Table 3. Chemical composition of molten iron after implementation of control 1

[0029] After melting, the temperature of the molten iron rises to 1550℃; after the molten iron in the furnace is left to stand for 5 minutes, the temperature of the molten iron is adjusted to 1500℃ before the water is discharged. During the water discharge process, a hanging scale is used to control the amount of molten iron discharged each time to be 1000 kg.

[0030] The spheroidizing treatment is carried out by the flushing method, and the spheroidizing agent is added to the spheroidizing bag on the side of the furnace body. The Mg content of the spheroidizing agent is 5.8%, the RE content is 1.5%, the particle size of the spheroidizing agent is 15-25 mm, and the amount of the spheroidizing agent added is 9.5 kg.

[0031] After tamping, a primary inoculant is added for primary inoculation. The primary inoculant is a silicon-barium alloy with a particle size of 3-8 mm, and the amount of the primary inoculant added is 4 kg.

[0032] During the primary inoculation, the spheroidizing package is compositely strengthened with Sb, Sn and Cu alloys, and Sb, Sn and Cu are added to the side of the spheroidizing package where no spheroidizing agent is added; wherein, the amount of Sb added is 100g; the amount of Sn added is 100g; and the amount of Cu added is 5.5kg.

[0033] After measuring that the molten iron temperature is 1498°C, the water is discharged and secondary inoculation is carried out along the flow. The secondary inoculant uses a silicon-barium alloy with a particle size of 3-8mm and a sulfur-oxygen inoculant with a particle size of 2-6mm. The amount of silicon-barium alloy in the secondary inoculant is 3kg, and the amount of sulfur-oxygen inoculant is 1.5kg. The molten iron obtained after the secondary inoculation is the final molten iron.

[0034] The chemical composition of the final molten iron was analyzed by direct reading spectrometer. The analysis results are shown in Table 4.

[0035] Table 4. Chemical composition of molten iron in implementation 1

[0036] It can be seen from Table 4 that the chemical composition of the final molten iron is qualified. Samples are taken from the final molten iron and poured into a thermal analysis sample cup for solidification. The cooling curve of the final molten iron is collected by a thermal analyzer. The cooling curve is analyzed by thermal analysis software. According to the analysis results, the dynamic eutectic index of the final molten iron is controlled to be 0.79, the inoculation index is 46, the shrinkage index is 0.38, and the liquidus carbon equivalent is 4.1. It can be seen from the above results that the quality of the final molten iron is qualified.

[0037] Control the thickness of the coated sand layer to 5-6mm and the temperature of the iron mold to 100-150℃. After the upper and lower iron molds are combined, stick the pouring cup at the sprue position and control the pouring cup height to 200㎜. The final molten iron with qualified chemical composition and quality is poured into the iron mold from the pouring cup, and the pouring temperature is controlled to be 1405°C. The weight of the final molten iron added to each iron mold during pouring is 80kg; during the pouring process, 0.08kg of Ce-containing inoculant is added to each iron mold, and the Si content of the Ce-containing inoculant is 72% and the Ce content is 1.9%; after the final molten iron is poured into the iron mold, the cooling rate of the final molten iron is 0.63°C / S; The whole process from spheroidization inoculation to pouring takes 6.5 minutes. After the final molten iron pouring is completed, the pouring cup is removed after the molten iron in the pouring cup solidifies. The casting is taken out of the box within 20 minutes after the pouring is completed. The casting temperature is 700℃ when it is unpacked. After unpacking, it is air-cooled to room temperature. The casting was heated to 900°C in a furnace at a heating rate of 10°C / min and kept at that temperature for 3 hours for normalizing treatment. The casting after normalizing treatment was first forced to be atomized and cooled for 4 minutes, and then kept at a temperature of 500°C for 4 hours for tempering treatment. After completion, it was air-cooled to room temperature to obtain a QT1050-5 crankshaft casting.

[0038] Forced atomization cooling is carried out in a mist cooling device, the atomization volume of the ultrasonic atomizer mist outlet is 90ml / min, and the wind speed of the fan is 8m / s.

[0039] The crankshaft casting obtained in this embodiment has a spheroidization grade of 2, a graphite size of 7, a pearlite content of 90%, a lamellar spacing of 258nm, and a hardness of 294HB. Example 2

[0040] The scrap steel in this embodiment is the plate-shaped steel head produced by the steel structure factory, and the recycled materials are the recycled materials produced by the pouring system during the pouring process. The materials of the raw materials are Q235 and Q345. The contents of various elements in the scrap steel are shown in Table 5.

[0041] Table 5. Element contents in scrap steel of Example 2

[0042] 1700 kg of the scrap steel and 300 kg of recycled materials in Table 5 were added into a medium frequency electric furnace to heat and melt molten iron. During the heating process, 68 kg of low-sulfur recarburizer and 18 kg of high-purity silicon carbide were added. After the molten iron was melted to 1500°C, the chemical composition of the molten iron was analyzed by direct reading spectrometer as shown in Table 6.

[0043] Table 6. Chemical composition of molten iron during smelting in Implementation 2

[0044] According to the analysis results of the direct reading spectrometer, the chemical composition of the molten iron is controlled as shown in Table 7 by adding carburizer, ferrosilicon alloy and ferromanganese alloy.

[0045] Table 7. Chemical composition of molten iron after implementing control 2

[0046] The entire smelting process takes 45 minutes. After melting, the temperature of the molten iron rises to 1550°C. After the molten iron in the furnace has been allowed to stand for 3 minutes, the temperature of the molten iron is adjusted to 1510°C and the water is immediately tapped. During the tapping process, a hanging scale is used to weigh the molten iron, which is 1000kg.

[0047] The spheroidizing treatment is carried out by the flushing method, and the spheroidizing agent is added to the spheroidizing bag on the side of the furnace body. The Mg content of the spheroidizing agent is 5.8%, the RE content is 1.2%, the particle size of the spheroidizing agent is 15-25 mm, and the amount of the spheroidizing agent added is 9.5 kg.

[0048] After tamping, a primary inoculant is added for primary inoculation. The primary inoculant is a silicon-barium alloy with a particle size of 3-8 mm, and the amount of the primary inoculant added is 4 kg.

[0049] During the primary inoculation, the spheroidizing package was compositely strengthened with Sb, Sn and Cu alloys. Sb, Sn and Cu were added to the side of the spheroidizing package where no spheroidizing agent was added. Among them, the amount of Sb added was 110g; the amount of Sn added was 110g; and the amount of Cu added was 5.5kg.

[0050] After measuring that the molten iron temperature is 1510°C, the water is discharged and secondary inoculation is carried out along the flow. The secondary inoculant uses a silicon-barium alloy with a particle size of 3-8mm and a sulfur-oxygen inoculant with a particle size of 2-6mm. The amount of silicon-barium alloy in the secondary inoculant is 3kg, and the amount of sulfur-oxygen inoculant is 1.5kg. The molten iron obtained after the secondary inoculation is the final molten iron.

[0051] The chemical composition of the final molten iron was analyzed by direct reading spectrometer. The analysis results are shown in Table 8.

[0052] Table 8. Chemical composition of molten iron in implementation 2

[0053] It can be seen from Table 8 that the chemical composition of the final molten iron is qualified. Samples were taken from the final molten iron, poured into a thermal analysis sample cup for solidification, and the cooling curve of the final molten iron was collected by a thermal analyzer. The cooling curve was analyzed by thermal analysis software. According to the analysis results, the dynamic eutectic index of the final molten iron was controlled to be 0.76, the inoculation index was 41, the shrinkage index was 0.35, and the liquidus carbon equivalent was 4.2. The above indicators show that the quality of the final molten iron is qualified.

[0054] Control the thickness of the coated sand layer to 5-6mm and the temperature of the iron mold to 100-150℃. After the upper and lower iron molds are combined, stick the pouring cup at the sprue position and control the pouring cup height to 200㎜. The final molten iron with qualified chemical composition and quality is poured into the iron mold from the pouring cup, the pouring temperature is 1408℃, and the weight of the final molten iron added to each iron mold during pouring is 80kg; 0.08kg of Ce-containing inoculant is added during the pouring process, and the Si content of the Ce-containing inoculant is 71.8% and the Ce content is 1.9%; after the final molten iron is poured into the iron mold, the cooling rate of the final molten iron is 0.62℃ / S; The whole process from spheroidization inoculation to pouring took 6.9 minutes. After the molten iron was poured, the pouring cup was removed after the molten iron solidified. The castings were unpacked and taken out within 20 minutes after pouring. The casting temperature was 700℃ when unpacking, and they were air-cooled to room temperature after unpacking. The casting was heated to 880°C in a furnace at a heating rate of 10°C / min and kept at that temperature for 4 hours for normalizing. The casting after normalizing was first forced to be atomized and cooled for 4 minutes, then kept at 550°C for 6 hours for tempering. After completion, it was air-cooled to room temperature to obtain a QT1050-5 crankshaft casting.

[0055] Forced atomization cooling is carried out in a mist cooling device, the atomization volume of the ultrasonic atomizer mist outlet is 75ml / min, and the wind speed of the fan is 5m / s.

[0056] The crankshaft casting obtained in this embodiment has a spheroidization grade of 2, a graphite size of 7, a pearlite content of 85%, a lamellar spacing of 180nm, and a hardness of 288HB. Example 3

[0057] The scrap steel in this embodiment is the plate-shaped steel head produced by the steel structure factory, and the recycled materials are the recycled materials produced by the pouring system during the pouring process. The materials of the raw materials are Q235 and Q345. The contents of various elements in the scrap steel are shown in Table 9.

[0058] Table 9. Element contents in scrap steel of Example 3

[0059] 1700 kg of the scrap steel and 300 kg of recycled materials in Table 9 were added into a medium frequency electric furnace to heat and melt molten iron. During the heating process, 59.5 kg of low-sulfur recarburizer and 13.6 kg of high-purity silicon carbide were added. After the molten iron was melted to 1500°C, the chemical composition of the molten iron was analyzed by direct reading spectrometer as shown in Table 10.

[0060] Table 10. Chemical composition of molten iron during smelting in Implementation 3

[0061] According to the analysis results of the direct reading spectrometer, the chemical composition of the molten iron was controlled as shown in Table 11 by adding carburizer, ferrosilicon alloy and ferromanganese alloy.

[0062] Table 11. Chemical composition of molten iron after implementing 3 controls

[0063] The entire smelting process takes 50 minutes. After melting, the temperature of the molten iron rises to 1550°C. The molten iron in the furnace is allowed to stand for 4 minutes, the temperature of the molten iron is adjusted to 1510°C, and then the water is discharged. During the discharge process, a hanging scale is used to weigh the molten iron, which is 1000kg.

[0064] The spheroidizing treatment is carried out by the flushing method, and the spheroidizing agent is added to the spheroidizing bag on the side of the furnace body. The Mg content of the spheroidizing agent is 5%, the RE content is 2%, the particle size of the spheroidizing agent is 15-25 mm, and the amount of the spheroidizing agent added is 9.5 kg.

[0065] After tamping, a primary inoculant is added for primary inoculation. The primary inoculant is a silicon-barium alloy with a particle size of 3-8 mm, and the amount of the primary inoculant added is 4 kg.

[0066] During the primary inoculation, the spheroidizing package is compositely strengthened with Sb, Sn and Cu alloys, and Sb, Sn and Cu are added to the side of the spheroidizing package where no spheroidizing agent is added; wherein, the amount of Sb added is 50g; the amount of Sn added is 150g; and the amount of Cu added is 5kg.

[0067] After measuring that the molten iron temperature is 1510°C, the water is discharged and secondary inoculation is carried out along the flow. The secondary inoculant uses a silicon-barium alloy with a particle size of 3-8mm and a sulfur-oxygen inoculant with a particle size of 2-6mm. The amount of silicon-barium alloy in the secondary inoculant is 3kg, and the amount of sulfur-oxygen inoculant is 1.5kg. The molten iron obtained after the secondary inoculation is the final molten iron.

[0068] The chemical composition of the final molten iron was analyzed by direct reading spectrometer. The analysis results are shown in Table 12.

[0069] Table 12. Chemical composition of molten iron after implementation 3

[0070] As can be seen from Table 12, the C content in the final molten iron is 3.62%, which exceeds the range of 3.5-3.6% of the C content in the final molten iron, so the chemical composition of this batch of final molten iron is unqualified. The final molten iron with unqualified chemical composition is used as recycled material in the raw materials of Examples 4 and 5. Example 4

[0071] The raw materials of this embodiment are the plate-shaped steel heads produced by the steel structure factory and the recycled materials produced in Example 3, wherein the plate-shaped steel heads produced by the steel structure factory are scrap steel, and the materials of the raw materials are Q235 and Q345. The contents of various elements in the scrap steel are shown in Table 13.

[0072] Table 13. Element contents in scrap steel of Example 4

[0073] 1000 kg of the scrap steel in Table 13 and 1000 kg of the recycled materials produced in Example 3 were added to a medium frequency electric furnace to heat and melt the molten iron. The entire smelting process took 45 minutes.

[0074] During the heating process, 40 kg of low-sulfur recarburizer and 8 kg of high-purity silicon carbide were added; after the molten iron was melted to 1500°C, the chemical composition of the molten iron was analyzed by direct reading spectrometer as shown in Table 14.

[0075] Table 14. Chemical composition of molten iron during smelting in Implementation 4

[0076] According to the analysis results of the direct reading spectrometer, the chemical composition of the molten iron is controlled as shown in Table 15 by adding carburizer, ferrosilicon alloy and ferromanganese alloy.

[0077] Table 15. Chemical composition of molten iron after implementing 4 controls

[0078] After melting, the temperature of the molten iron rises to 1550℃; after the molten iron in the furnace is left to stand for 4.8 minutes, the temperature of the molten iron is adjusted to 1520℃ before the water is discharged. During the water discharge process, a hanging scale is used to control the amount of molten iron discharged each time to be 1000 kg.

[0079] The spheroidizing treatment is carried out by the flushing method, and the spheroidizing agent is added to the spheroidizing bag on the side of the furnace body. The Mg content of the spheroidizing agent is 6%, the RE content is 2%, the particle size of the spheroidizing agent is 15-25 mm, and the amount of the spheroidizing agent added is 9.5 kg.

[0080] After tamping, a primary inoculant is added for primary inoculation. The primary inoculant is a silicon-barium alloy with a particle size of 3-8 mm, and the amount of the primary inoculant added is 4 kg.

[0081] During the primary inoculation, the spheroidizing package is compositely strengthened with Sb, Sn and Cu alloys, and Sb, Sn and Cu are added to the side of the spheroidizing package where no spheroidizing agent is added; wherein, the amount of Sb added is 150g; the amount of Sn added is 50g; and the amount of Cu added is 5kg.

[0082] After measuring that the molten iron temperature is 1500°C, the water is discharged and secondary inoculation is carried out along the flow. The secondary inoculant uses a silicon-barium alloy with a particle size of 3-8mm and a sulfur-oxygen inoculant with a particle size of 2-6mm. The amount of silicon-barium alloy in the secondary inoculant is 3kg, and the amount of sulfur-oxygen inoculant is 1.5kg. The molten iron obtained after the secondary inoculation is the final molten iron.

[0083] The chemical composition of the final molten iron was analyzed by direct reading spectrometer. The analysis results are shown in Table 16.

[0084] Table 16. Chemical composition of molten iron after implementation 4

[0085] It can be seen from Table 16 that the chemical composition of the final molten iron is qualified. Samples are taken from the final molten iron and poured into a thermal analysis sample cup for solidification. The cooling curve of the final molten iron is collected by a thermal analyzer. The cooling curve is analyzed by thermal analysis software. According to the analysis results, the dynamic eutectic index of the final molten iron is controlled to be 0.82, the inoculation index is 33, the shrinkage index is 0.21, and the liquidus carbon equivalent is 4.18. From the above results, it can be seen that the quality of the final molten iron is qualified.

[0086] Control the thickness of the coated sand layer to 5-6mm and the temperature of the iron mold to 100-150℃. After the upper and lower iron molds are combined, stick the pouring cup at the sprue position and control the pouring cup height to 150㎜. The final molten iron with qualified chemical composition and quality is poured into the iron mold from the pouring cup, and the pouring temperature is controlled to be 1420°C. The weight of the final molten iron added to each iron mold during pouring is 80kg; 0.08kg of Ce-containing inoculant is added to each iron mold during the pouring process, and the Si content of the Ce-containing inoculant is 68% and the Ce content is 2%; after the final molten iron is poured into the iron mold, the cooling rate of the final molten iron is 0.65°C / S; The whole process from spheroidization inoculation to pouring takes 7 minutes. After the final molten iron is poured, the pouring cup is removed after the molten iron in the pouring cup solidifies. The casting is unpacked and taken out within 24 minutes after pouring. The casting temperature is 610℃ when unpacking. After unpacking, it is air-cooled to room temperature. The casting was heated to 890°C in a furnace at a heating rate of 10°C / min and kept at that temperature for 3.3 hours for normalizing treatment. The casting after normalizing treatment was first forced to be atomized and cooled for 3.5 minutes, and then kept at a temperature of 530°C for 8 hours for tempering treatment. After completion, it was air-cooled to room temperature to obtain a QT1050-5 crankshaft casting.

[0087] Forced atomization cooling is carried out in a mist cooling device, the atomization volume of the ultrasonic atomizer mist outlet is 80ml / min, and the wind speed of the fan is 6m / s.

[0088] The crankshaft casting obtained in this embodiment has a spheroidization grade of 2, a graphite size of 8, a pearlite content of 93%, a lamellar spacing of 224nm, and a hardness of 274HB. Example 5

[0089] The raw materials of this embodiment are the plate-shaped steel heads produced by the steel structure factory and the recycled materials produced in Example 3, wherein the plate-shaped steel heads produced by the steel structure factory are scrap steel, and the materials of the raw materials are Q235 and Q345. The contents of various elements in the scrap steel are shown in Table 17.

[0090] Table 17. Element content in scrap steel of Example 5

[0091] 1400 kg of the scrap steel in Table 17 and 600 kg of the recycled material produced in Example 3 were added to a medium frequency electric furnace to heat and melt molten iron. During the heating process, 53.2 kg of low-sulfur recarburizer and 16.8 kg of high-purity silicon carbide were added. After the molten iron was melted to 1500°C, the chemical composition of the molten iron was analyzed by direct reading spectrometer as shown in Table 18.

[0092] Table 18. Chemical composition of molten iron during smelting in Implementation 5

[0093] According to the analysis results of the direct reading spectrometer, the chemical composition of the molten iron is controlled as shown in Table 19 by adding carburizer, ferrosilicon alloy and ferromanganese alloy.

[0094] Table 19. Chemical composition of molten iron after implementing 5 controls

[0095] The entire smelting process takes 44 minutes. After melting, the temperature of the molten iron rises to 1550℃. After the molten iron in the furnace is left to stand for 4.8 minutes, the temperature of the molten iron is adjusted to 1515℃ before the water is discharged. During the water discharge process, a hanging scale is used to control the amount of molten iron discharged each time to be 1000 kg.

[0096] The spheroidizing treatment is carried out by the flushing method, and the spheroidizing agent is added to the spheroidizing bag on the side of the furnace body. The Mg content of the spheroidizing agent is 5.4%, the RE content is 1.6%, the particle size of the spheroidizing agent is 15-25 mm, and the amount of the spheroidizing agent added is 9.5 kg.

[0097] After tamping, a primary inoculant is added for primary inoculation. The primary inoculant is a silicon-barium alloy with a particle size of 3-8 mm, and the amount of the primary inoculant added is 4 kg.

[0098] During the primary inoculation, the spheroidizing package was compositely strengthened with Sb, Sn and Cu alloys. Sb, Sn and Cu were added to the side of the spheroidizing package where no spheroidizing agent was added. Among them, the amount of Sb added was 120g; the amount of Sn added was 80g; and the amount of Cu added was 6.2kg.

[0099] After measuring that the molten iron temperature is 1505°C, the water is discharged and secondary inoculation is carried out along the flow. The secondary inoculant uses a silicon-barium alloy with a particle size of 3-8mm and a sulfur-oxygen inoculant with a particle size of 2-6mm. The amount of silicon-barium alloy in the secondary inoculant is 3kg, and the amount of sulfur-oxygen inoculant is 1.5kg. The molten iron obtained after the secondary inoculation is the final molten iron.

[0100] The chemical composition of the final molten iron was analyzed by direct reading spectrometer. The analysis results are shown in Table 20.

[0101] Table 20. Chemical composition of molten iron after implementation 5

[0102] It can be seen from Table 20 that the chemical composition of the final molten iron is qualified. Samples are taken from the final molten iron and poured into thermal analysis sample cups for solidification. The cooling curve of the final molten iron is collected by a thermal analyzer. At the same time, the cooling curve is analyzed by thermal analysis software. According to the analysis results, the dynamic eutectic index of the final molten iron is controlled to be 0.85, the inoculation index is 42, the shrinkage index is 0.27, and the liquidus carbon equivalent is 4.12. From the above results, it can be seen that the quality of the final molten iron is qualified.

[0103] Control the thickness of the coated sand layer to 5-6mm and the temperature of the iron mold to 100-150℃. After the upper and lower iron molds are combined, stick the pouring cup at the sprue position and control the pouring cup height to 200㎜. The final molten iron with qualified chemical composition and quality is poured into the iron mold from the pouring cup, and the pouring temperature is controlled to be 1415°C. The weight of the final molten iron added to each iron mold during pouring is 80kg; during the pouring process, 0.08kg of Ce-containing inoculant is added to each iron mold, and the Si content of the Ce-containing inoculant is 70% and the Ce content is 1.7%; after the final molten iron is poured into the iron mold, the cooling rate of the final molten iron is 0.64°C / S; The whole process from spheroidization inoculation to pouring took 6.8 minutes. After the final molten iron was poured, the pouring cup was removed after the molten iron in the pouring cup solidified. The castings were unpacked and taken out within 24 minutes after pouring. The casting temperature was 689℃ when unpacking. After unpacking, the castings were air-cooled to room temperature. The casting was heated to 895°C in a furnace at a heating rate of 10°C / min and kept at that temperature for 3.9 hours for normalizing treatment. The casting after normalizing treatment was first forced to be atomized and cooled for 3 minutes, and then kept at a temperature of 536°C for 6 hours for tempering treatment. After completion, it was air-cooled to room temperature to obtain a QT1050-5 crankshaft casting.

[0104] Forced atomization cooling is carried out in a mist cooling device, the atomization volume of the ultrasonic atomizer mist outlet is 85ml / min, and the wind speed of the fan is 7m / s.

[0105] The crankshaft casting obtained in this embodiment has a spheroidization grade of 2, a graphite size of 7, a pearlite content of 93%, a lamellar spacing of 285nm, and a hardness of 307HB. Comparative Example 1

[0106] The crankshaft castings obtained in Example 1, Example 2, Example 4 and Example 5 were sampled and sent to a testing agency for testing. The test results are as follows: Figure 5 and Figure 6 The sample of Example 1 corresponds to result -1, the sample of Example 2 corresponds to result -2, the sample of Example 4 corresponds to result -3, and the sample of Example 5 corresponds to result -4.

[0107] Depend on Figure 6 It can be seen that the results of the tensile strength and elongation after fracture of the crankshaft castings obtained in Examples 1, 2, 4 and 5 of the present application are shown in Table 21.

[0108] Table 21. Crankshaft casting test results

[0109] It can be seen from the contents of Table 21 combined with the contents of Examples 1, 2, 4, and 5 that the crankshaft casting obtained in this application meets the requirements of grade QT1050-5.

[0110] The crankshaft casting obtained in Example 2 was sampled and observed under a microscope. The microstructure diagram is as follows Figure 7 As shown, Figure 7 (a) is the microstructure image after 2000 times magnification. Figure 7 (b) is the microstructure image after 10000 times magnification. Figure 7 (a) shows that the ductile iron structure consists of two parts. The general structure is pearlite with fine interlamellar spacing, while the bamboo-like structure appears in the red circle. Figure 7 As shown in (b), the red bamboo-leaf-shaped structure still contains pearlite, but the cementite is short rod-shaped or granular, indicating that the cementite is severely refined. Analysis shows that the bamboo-leaf-shaped pearlite grains are partially formed by atomization normalizing martensite, and the martensite is decomposed into pearlite structure containing fine cementite during subsequent tempering. Due to the severe refinement of pearlite, the strength and toughness of ductile iron are greatly improved.

Claims

1. A method for producing QT1050-5 crankshaft using all scrap steel, characterized in that: The following steps are involved: S1, smelting, adding raw materials into a medium frequency electric furnace to heat up and smelt molten iron, wherein the raw materials are scrap steel and recycled materials; During the heating process, 3.5-4.0% of the total weight of the scrap steel is added as a low-sulfur recarburizer and 0.8-1.5% of the total weight of the scrap steel is added; after the molten iron is melted to 1500°C, a direct reading spectrometer is used to analyze the chemical composition of the molten iron; According to the analysis results of the direct reading spectrometer, by adding carburizer, ferrosilicon alloy and ferromanganese alloy, the chemical composition of molten iron is controlled to be 3.65-3.75% C; 1.2-1.3% Si; 0.5-0.65% Mn; ≤0.020% S; ≤0.025% P; 0.1-0.15% Cr; 0.2-0.3% Cu; 0.015-0.02% Ni; The time of the whole smelting process is controlled to be ≤50min; after melting, the temperature of the molten iron rises to 1550℃; after the molten iron in the furnace is left to stand for 3-5 minutes, the temperature of the molten iron is adjusted to the outlet temperature of 1510±10℃ before the water is discharged; during the water discharge process, a hanging scale is used to control the amount of molten iron discharged each time; S2, spheroidizing treatment, primary inoculation and composite strengthening, spheroidizing treatment is carried out by flushing method, spheroidizing agent is added to the spheroidizing bag on the side of the furnace body, the Mg content of the spheroidizing agent is 5-6%, the RE content is 1-2%, the particle size of the spheroidizing agent is 15-25 mm, and the amount of the spheroidizing agent added is 0.95% of the weight of the molten iron; After tamping, a primary inoculant is added for primary inoculation, wherein the primary inoculant is a silicon-barium alloy with a particle size of 3-8 mm, and the amount of the primary inoculant added is 0.4% of the weight of the molten iron; While adding the primary inoculant, the spheroidizing bag is compositely strengthened with Sb, Sn and Cu alloys, and Sb, Sn and Cu are added to the side of the spheroidizing bag where the spheroidizing agent is not added; wherein, the amount of Sb added is 0.005-0.015% of the weight of the molten iron; the amount of Sn added is 0.005-0.015% of the weight of the molten iron; and the amount of Cu added is 0.5-0.65% of the weight of the molten iron; S3, secondary inoculation, after the completion of step S2, the temperature of the molten iron is measured and the water is discharged and the secondary inoculation is carried out with the flow, the secondary inoculant adopts a silicon-barium alloy with a particle size of 3-8mm and a sulfur-oxygen inoculant with a particle size of 2-6mm, the amount of the silicon-barium alloy in the secondary inoculant is 0.3% of the weight of the molten iron, and the amount of the sulfur-oxygen inoculant is 0.15% of the weight of the molten iron; the molten iron obtained after the secondary inoculation is the final molten iron; S4, chemical composition and quality control of the final molten iron, the chemical composition of the final molten iron is analyzed by direct reading spectrometer, when the C content of the final molten iron is 3.5-3.6%, the Si content is 2.25-2.35%, the Cu content is 0.75-0.85%, the Sn content is 0.008-0.015%, and the Sb content is 0.008-0.015%, the chemical composition is qualified, otherwise the chemical composition is unqualified; at the same time, a sample is taken from the final molten iron, poured into a thermal analysis sample cup for solidification, and the cooling curve of the final molten iron is collected by a thermal analyzer, and the cooling curve is analyzed by thermal analysis software. The quality of the final molten iron is controlled according to the analysis results. When the dynamic eutectic index in the final molten iron is 0.7-0.9, the inoculation index is 30-50, the shrinkage index is 0.2-0.45, and the liquidus carbon equivalent is 4.1-4.2, the quality is qualified, otherwise it is unqualified; S5, iron mold sand coating molding, control the thickness of the coating sand layer to 5-6mm, iron mold temperature to 100-150℃, after the upper and lower iron molds are combined, glue the pouring cup at the sprue position, and control the pouring cup height to 150-200㎜; S6, pouring, pouring the final molten iron with qualified chemical composition and quality in step S4 from the pouring cup into the iron mold, controlling the pouring temperature to be 1410±10°C, adding a Ce-containing inoculant with a weight of 0.1% of the weight of the final molten iron in the iron mold during the pouring process, wherein the Ce-containing inoculant has a Si content of 68-74% and a Ce content of 1.5%-2.0%; after the final molten iron is poured into the iron mold, the cooling rate of the final molten iron is 0.6-0.65°C / S; From step S2 to step S6, the whole process takes ≤7 minutes; S7, unpacking. After the molten iron is poured, the pouring cup is removed after the molten iron in the pouring cup solidifies. The casting is unpacked and taken out within 20-25 minutes after the pouring is completed. The casting temperature is 600-700℃ when unpacking. After unpacking, the casting is air-cooled to room temperature. S8, heat treatment, heating the casting obtained in step S7 to 880°C-900°C, keeping it at that temperature for 3-4 hours for normalizing treatment; firstly force atomization cooling of the casting after normalizing treatment for 3-4 minutes, then keeping it at that temperature for 4-8 hours at a temperature of 500-550°C for tempering treatment, and then air cooling it to room temperature to obtain QT1050-5 crankshaft casting.

2. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 1, characterized in that: The obtained crankshaft casting has a spheroidizing grade of 1-2, a graphite size of 6-8, a pearlite content of 80-95%, a lamellar spacing of 150-300nm, a tensile strength Rm≥1050MPa, an elongation of 5.5%-9%, and a hardness of 270-320HB.

3. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 1, characterized in that: The heating method in step S8 is heating along with the furnace, and the heating rate is 10°C / min.

4. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 1, characterized in that: The scrap steel has a C content of 0.2-0.4%, a Si content of 0.25-0.35%, a Mn content of ≤0.8%, a P content of ≤0.03%, and a S content of ≤0.02%.

5. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 1, characterized in that: The forced atomization cooling in step S8 is carried out in a mist cooling device, which is composed of a sealed box, a pipe frame and a fan. The sealed box is a rectangular structure; the pipe frame is arranged in the sealed box, and the fan is arranged on the pipe frame; there are two pipe frames and they are interconnected, the two pipe frames have the same shape and circumference, and the connection between the two pipe frames is in a "cross" shape; a number of oval-shaped mist outlets are evenly opened on the inner side of the pipe frame; the fan covers the mist outlet and is arranged on the pipe frame through a fixing clamp; a connecting pipe is also arranged at the center of the outer side of the two pipe connection, one end of the connecting pipe is connected to the inside of the pipe frame, and the other end passes through the sealed box and is arranged outside the sealed box; a drainage pipe connected to the inside of the sealed box is also provided at the bottom of the sealed box.

6. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 5, characterized in that: A lock buckle for hanging the casting is arranged at the center of the upper part of the pipeline frame.

7. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 5, characterized in that: One end of the connecting pipe passing through the sealing box and arranged outside the sealing box is connected with the mist outlet end of the ultrasonic atomizer, and the drain pipe is connected with the water inlet end of the ultrasonic atomizer.

8. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 5, characterized in that: A surface on the sealed box is movably arranged on the sealed box to form a box door.

9. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 7, characterized in that: The particle size of the water mist produced by the ultrasonic atomizer is 5μm; the atomization volume of the mist outlet is 75-90ml / min, and the wind speed of the fan is 5m / s-8m / s.

10. The method for producing a QT1050-5 crankshaft using all scrap steel according to claim 1, characterized in that: The final molten iron with unqualified chemical composition and / or quality in step S4 is returned to step S1 as recycled material.

Citation Information

Patent Citations

  • A method for producing cast QT950-4 crankshafts using all scrap steel

    CN109594010B